Systemic sclerosis sine scleroderma: a case report of anterior uveitis - T. Borges; J. Vilaça; S. Ferreira; I. Chora; S. Silva; C. Dias (PAGEPress Publications, 2015)
Systemic sclerosis (SSc) sine scleroderma (ssSSc) is characterized by the absence of skin involvement, despite other manifestations of systemic sclerosis are present. It is not known whether sSSc represents a forme fruste of limited cutaneous SSc or a distinct entity, but the 2013 American College of Rheumatology/European League Against Rheumatism criteria for the classification of SSc have considered SSc without skin involvement to be a distinct subset. The authors present the case of a 70-year old female that was referred for a consultation for Raynaud's phenomenon and a chronic anterior uveitis (CAU). She had a history of dysphagia, diffuse pulmonary emphysema and a biopsy-documented fibrosis of the upper lobes, and an idiopathic non-ischemic dilated cardiomyopathy with severe left ventricle systolic dysfunction and left bundle branch block. Anti-nuclear and anti-centromere antibodies were positive, while manometry revealed distal esophageal hypomotility. After establishing the diagnosis of ssSSc and starting immunosuppression, the ocular disease improved, while the lung and heart diseases remained stable. This case underlines that it is very important to suspect SSc when CAU is present and/or skin thickening is absent. To our knowledge, this is the first report of CAU in a patient with ssSSc.